A structure-based in silico analysis of the Kell blood group system - Mayr, Gabriele; Bublitz, Maike; Steiert, Tim A.; Löscher, Britt-Sabina; Wittig, Michael; ElAbd, Hesham; Gassner, Christoph; Franke, Andre (Frontiers in Immunology, 2024)
Kell is one of the most complex blood group systems, with a highly polymorphic genetic background. Extensive allelic variations in the KEL gene affect the encoded erythrocyte surface protein Kell. Genetic variants causing aberrant splicing, premature termination of protein translation, or specific amino acid exchanges lead to a variety of different phenotypes with altered Kell expression levels or changes in the antigenic properties of the Kell protein. Using an in silico structural model of the Kell protein, we analyzed the biophysical and structural context of all full-length Kell variants of known phenotype. The results provided insights regarding the 3D co-localization of antigenic Kell variants and led us to suggest several conformational epitopes on the Kell protein surface. We found a number of correlations between the properties of individual genetic variants in the Kell protein and their respective serological phenotypes, which we used as a search filter to predict potentially new immunogenic Kell variants from an in-house whole exome sequencing dataset of 19,772 exomes. Our analysis workflow and results aid blood group serologists in predicting whether a newly identified Kell genetic variant may result in a specific phenotype.